COVID-19 Burden on HIV Patients Attending Antiretroviral Therapy in Addis Ababa, Ethiopia: A Multicenter Cross-Sectional Study - Chilot, Dagmawi; Woldeamanuel, Yimtubezinash; Manyazewal, Tsegahun (Frontiers in Medicine, 2022)
Background: There has been promising progress towards screening, testing, and retaining HIV patients in care in Ethiopia. Concern exists that possible disruptions in HIV programs due to COVID-19 could result in more HIV-related mortality and new HIV infections. This study aimed to investigate the real-time burden of COVID-19 on HIV patients attending ART. Methods: We conducted a facility-based, multicentre, cross-sectional study among HIV patients attending antiretroviral therapy in 10 healthcare facilities in Addis Ababa, Ethiopia, in the COVID-19 pandemic period. Result: A total of 212 patients with HIV were included. Participants who missed visits for refill were 58 (27.4%). When the effects of other independent variables on appointments/visits for refill were controlled, the following characteristics were found to be the most important pridictors of missed appointments (P < 0.05): age ≥55 [AOR=6.73, 95% CI (1.495-30.310)], fear of COVID-19 [AOR=24.93, 95% CI (2.798-222.279)], transport disruption [AOR=4.90, 95% CI (1.031-23.174)], reduced income for traveling to health facility [AOR=5.64, 95% CI (1.234-25.812)], and limited access to mask [AOR=7.67, 95% CI (1.303-45.174)], sanitizer [AOR=0.07, 95% CI (0.007-0.729)] and non-medical support [AOR=2.32, 95% CI (1.547-12.596)]. The participants were well aware of the COVID-19 preventive measures. The most costly COVID-19 preventive measures that cause financial burden to the patients were costs for buying facemasks (63.7%), disinfectants (55.2) and sops for handwashing (22.2). Participants who missed follow-up diagnostic tests were 56 (26.4%). Variables which were found to be statistically significant include the following: age ≥55 [AOR=0.22, 95% CI (0.076-0.621)], partial lockdown [AOR=0.10, 95% CI (0.011-0.833)], limited access to health services [AOR=0.15, 95% CI (0.045-0.475)], reduced income for traveling to health facility [AOR=0.18, 95% CI (0.039-0.784)], and unable to get mask [AOR=0.12, 95% CI (0.026-0.543)]. Participants who missed counseling services were 55 (25.9%). In multivariate logistic regression the following were statisticaly significant: age ≥55 [AOR= 0.21, 95% CI (0.078-0.570)], fear of COVID-19 [AOR= 0.11, 95% CI (0.013-0.912)], reduced income [AOR= 0.17, 95% CI (0.041-0.699)], unable to get face mask [AOR= 0.19, 95%CI (0.039-0.959)], and partial lockdown [AOR= 0.08, 95% CI (0.008-0.790)]. Conclusions: COVID-19 had a significant burden on HIV patients to attend their routine clinical care and treatment.